The ILE462VAL polymorphism of the cytochrome P450 CYP1A1 gene among Tundra Nenets in Yamalo-Nenets Autonomous Okrug, Nganasans in the Taimyr Peninsula and Russians in Siberia - R. P. Tiis; L. P. Osipova; T. V. Churkina; L. E. Tabikhanova; D. V. Lichman; E. N. Voronina; M. L. Filipenko (Вавиловский журнал генетики и селекции)
The work concerns a polymorphism of the cytochrome Р450 CYP1A1 gene, the CYP1A1*2C variant (Ile462Val, rs1048943). This substitution results in a two- fold increase in enzyme activity, which leads to accumulation of active intermediates and increases the risk of DNA mutations and chemically induced carcinogenesis. It has been demonstrated that the 462Val allele may be a risk factor in some oncological and other multifactorial diseases. This study was performed on Tundra Nenets in Yamalo-Nenets Autonomous Okrug (N = 271), Nganasans in the Taimyr Peninsula (N = 186) and Russians in North Siberia (N = 267). The cohorts did not include descendants of mixed marriages. Genotyping was performed using Real-Time PCR with competitive TaqMan allele-specific probes. The frequency of the 462Val allele in the Tundra Nenets cohort was 23.8 % (95 % CI 20.4–27.6 %), which corresponds to the frequency range found in East Asian populations and is higher than the values typical of European populations. The 462Val allele frequency in the Russian cohort was 5.8 % (95 % CI 4.1–8.1 %), which corresponds to the frequency range of European populations. The 462Val allele frequency in the Nganasans cohort was 39.0 % (95 % CI 34.2–44.0 %), which is higher than the frequencies found in European, Asian and African populations. Frequencies of the  462Val variant close to that in Nganasans have been observed in Greenland Inuits, native Americans as a whole and the Southern Chinese. A high-frequency occurrence of the 462Val allele among Tundra Nenets and Nganasans may be indicative of a populationwide risk of diseases influenced by this genetic polymorphism, especially when traditional mainstays are gone or previously unknown ecotoxicants appear in the areas.